Depth Profile Analysis of Thin Oxide Layers on Polycrystalline Fe-Cr - Zijlstra, Gerrit; Šamořil, Tomáš; Tesařová, Hana; Ocelík, Václav; De Hosson, Jeff Th M (Microscopy and microanalysis, 2020)
Surfaces of polycrystalline ferritic Fe-Cr steel with grain sizes of about 13 µm in diameter were investigated with surface sensitive techniques. Thin oxide layers, with a maximum thickness of about 100 nm, were grown by oxidation in air at temperatures up to 450°C and were subsequently characterized using time-of-flight secondary ion mass spectrometry (TOF-SIMS) and atomic force microscopy. Correlative microscopy was applied, which allows for element-specific depth profiles on selected grains with a particular crystal orientation. A strong correlation between the grain orientation and the thickness of the oxide layer was found. The sequence in the oxidation growth rate of ferritic Fe-Cr steel crystal planes is found to be {011} > {111} > {001}, which is unexpectedly opposed to known Fe-based systems. Moreover, for the first time, the Cr/Fe ratio throughout the oxide layer has been determined per grain orientation. A clear order from high to low of {001} > {111} > {011} was detected.
Keywords: corrosion; polycrystalline; TOF-SIMS; EBSD; Fe-Cr steel